When rituals go wrong: mistakes, failure and the dynamics of ritual - Hüsken, Ute (Numen Book Ser., 2007)
This volume investigates the implications of breaking ritual rules, of failed performances and of the extinction of ritual systems. The essays thus break new ground in the comparative analysis of rituals and introduce new perspectives to ritual studies.